Problem-Based Learning Dan Pengembangan Higher-Order Thinking Skills Pada Mahasiswa Kedokteran: Tinjauan Literatur - Ekawati Rini Wulansari; Amanah Eva Fidusia; Erika Agustianti; Firda Asma’ul Husna; Siti Darifah; erni Trisnasari; Luluk Hermawati (Jurnal Inovasi Pendidikan Dan Pembelajaran, 2025)
Modern medical education emphasizes not only the mastery of medical knowledge but also the development of higher-order thinking skills (HOTS), including critical thinking, problem solving, and self-directed learning (SDL). To achieve these learning outcomes, Problem-Based Learning (PBL) has become one of the most widely implemented instructional strategies in medical curricula worldwide. This literature-based study aims to systematically examine the contribution of PBL in medical education to the enhancement of students’ HOTS. The Methods was using A comprehensive literature search was conducted through PubMed, Scopus, and Google Scholar using the keywords “Problem-Based Learning,” “Medical Education,” “Higher-Order Thinking Skills,” “Critical Thinking,” “Problem solving,” and “Self-Directed Learning.” Inclusion criteria consisted of publications from 2015–2025, empirical research, systematic reviews, or literature reviews within the field of medical education. The Results are The findings indicate that PBL in medical education significantly improves critical thinking by fostering analytical and evaluative skills, enhances problem-solving ability through authentic clinical case scenarios, and supports self-directed learning by promoting learner autonomy in identifying study needs and accessing scientific evidence. The success of PBL depends on the quality of case scenarios, the role of tutors as facilitators, and the readiness of students to engage actively in the learning process. The Conclusion is Evidence from the literature highlights that Problem-Based Learning plays a pivotal role in developing higher-order thinking skills among medical students. Integrating PBL systematically into medical curricula—supported by adequate learning resources and trained facilitators—strengthens lifelong learning competencies and prepares students to face the complex challenges of modern healthcare.